(3QSGdI aj GdCSWQdGH (B( (3Edi CHj jhSa GdMSf Hf ESQGFjd(B)s - (3EHQGgje Hf SfGf Hf KGHJ Hf bQI Hf eQhGf Hf KGHJ, CHh ESMGb GdMqQGfj Ke GdHZOGOj,J (B335 (3g` s
(3ChdgG (B:s
(3GdfGS jG SjOi jXfhf Gf GdGSWQdGH ccQg ef SJ hJhgehG Pdc ef cJGH HWdjehS ai JSWjM GdcQI hdjS GdGeQ cPdc hdG Yed GdGSWQdGH Ydi Cf fbdH GdcQI s
(3BNQgG (B:s
(3aRGhjI aSO eSGhjI dRGhjI bHQ hdPdc jchf bhS Ob THjgg HbhS bQ hPdc eG GQOfG Gf fHjf JeJ GdebGdI dEHQGgje Hf SfGf ai GdGSWQdGH hddg GdMeO s
(3HgG TcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B42 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B36s
Keywords: (3Gdadcs